Earthquake Environmental Effects and Building Properties Controlling Damage Caused by the 6 February 2023 Earthquakes in East Anatolia - Spyridon Mavroulis; Ioannis Argyropoulos; Emmanuel Vassilakis; Panayotis Carydis; Efthymis Lekkas (Geosciences, 2023)
On 6 February 2023, East Anatolia was devastated by two major earthquakes resulting in hundreds of thousands of collapses and tens of thousands of human casualties. This paper investigates the factors related to building properties and earthquake environmental effects (EEEs) that contributed to the building damage grade and distribution in southeastern Turkey. In regards to the building construction properties, the loose enforcement of the building code, the random urban planning solutions and the poor construction standards are the main construction deficiencies that led to one of the largest disasters in Turkey’s recent history. Regarding geological factors, the triggering of primary and secondary EEEs largely shaped the grade and distribution of damage. Where coseismic surface ruptures intersected with the built environment, heavy to very heavy structural damage was observed. This was evident in many cases along the ruptured segments of the East Anatolian Fault Zone (EAFZ). Liquefaction observed close to waterbodies caused damage typical of building foundation load-bearing capacity loss. The earthquake-triggered landslides affected mainly mountainous and semi-mountainous settlements characterized with pre-earthquake high related susceptibility. The high susceptibility to generation of EEEs was extensively confirmed in many cases resulting in extensive damage. The provided information highlights the importance of such studies for hazard mitigation and disaster risk reduction.